GABAergic Input From the Basal Forebrain Promotes the Survival of Adult-Born Neurons in the Mouse Olfactory Bulb - Hanson, Elizabeth; Swanson, Jessica; Arenkiel, Benjamin R. (Frontiers in Neural Circuits, 2020)
A unique feature of the olfactory system is the continuous generation and integration of new neurons into adulthood. Adult-born neuron survival and integration is dependent on activity and sensory experience, which is largely mediated by early synaptic inputs that adult-born neurons receive upon entering the olfactory bulb (OB). As in early postnatal development, the first synaptic inputs onto adult-born neurons are GABAergic. However, the specific sources of early synaptic GABA and the influence of specific inputs on adult-born neuron development are poorly-understood. Here we use retrograde and anterograde viral tracing to reveal robust GABAergic projections from the basal forebrain horizontal limb of the diagonal band of Broca (HDB) to the granule cell layer (GCL) and glomerular layer (GL) of the mouse OB. Whole-cell electrophysiological recordings indicate that these projections target interneurons in the GCL and GL, including adult-born granule cells (abGCs). Recordings from birth-dated abGCs reveal a developmental time course in which HDB GABAergic input onto abGCs emerges as the neurons first enter the OB and strengthens throughout the critical period of abGC development. Finally, we show that removing GABAergic signaling from HDB neurons results in decreased abGC survival. Together these data show that GABAergic projections from the HDB synapse onto immature abGCs in the OB to promote their survival through the critical period, thus representing a source of long-range input modulating plasticity in the adult OB.